ANALISIS YURIDIS TERHADAP PERAN DAN KEDUDUKAN MAHKAMAH PARTAI POLITIK DALAM MENYELESAIKAN SENGKETA DUALISME PARTAI POLITIK - Kamal, Mustafa; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Political parties are the only organization that specifically has a fundamental duty to manifest social power into political power. The journey of life of political parties in Indonesia are often faced with various problems, such as political parties to organize themselves to be free of the threat of division; how the relationship between political parties and the people supporting; how the role of ideology in the life of political parties to obtain material means; and how the role of political parties for the smooth rotation of the party machine. This study aims to find out what the urgency of resolving disputes through the Court duality of political parties and how the existence of a party dispute resolution duality in the Political Parties Court.This type of research is a normative legal research. In this study, the author further discusses about the legal principles pertaining to the juridical analysis of the Court's role and position of the Party in a dispute myelesaikan dualism of political parties. The author uses secondary data sources, which are the source of data obtained from the literature, include the official documents, books, research results are tangible reports and so on.Results of this study was to clarify the urgency Court Parties in dispute resolution stewardship of a political party can be seen from the Court's authority in the party to decide disputes stewardship bersipat final and binding sebagaiman set in AD / ART and Article 32 of Law No. 2 of 2011 on Political Parties. Then the existence of the Court Party in internal party dispute settlement in Indonesia, recognized in Article 32 of Law No. 2 of 2011 on the Amendment of Act No. 2 of 2008 on Political Parties, and also strengthened in the development of jurisprudence judges.The legal consequences of the nature of the Court's ruling party is final and binding, but contribute also settled by the District Court with the decision that is the first and the last, and can only be appealed to the Supreme Court. This resulted in non-synchronization between Article 32 and Article 33 which could undermine the existence of the Party Court to exercise its authority.KEYWORDS - Analysis of Juridical, Court, Political Party, Dispute dualism.